Find equivalent value on different ranges - math

So...
I've been banging my head on the wall over this problem for a few days now, but still couldn't find a solution.
I have two ranges of numbers
A -> B
C -> D
A given number (x) is on the A -> B range.
I need to find it's equivalent in the C -> D range.
eg:
A -> B = (2 -> 4)
C -> D = (-148 -> -50)
x = 2.3
What is the equivalent value on the (-148 -> -50) range?

Your requirements are a bit loose, but I would be tempted to believe you want to find an affine transformation from the interval [2;4] to [-148;-50].
Calling f(x) = a.x + b this transformation, you have:
f(2) = 2.a + b = -148
f(4) = 4.a + b = -50
=> 2.f(2) = 4.a + 2.b = -296
=> 2.f(2) - f(4) = b = -246
=> a = (-148 - b)/2 = 49
=> f(x) = 49.x - 246
So the point you are looking for would be f(2.3) = -133.3

You can use ((X - A) * (D - C) / (B - A)) + C.
Size of first range is: B - A
Size of second range is: D - C
Ratio between (X - A) and (Y - C) should be proportional to that of (B - A) and (D - C).

Related

How to pattern match 0.0 in SML? [duplicate]

This question already has an answer here:
Why can't I compare reals in Standard ML?
(1 answer)
Closed 4 years ago.
I have the following code:
datatype complex = RealImg of real * real | Infinity;
fun divisionComplex(RealImg(a, b), RealImg(0.0, 0.0)) = Infinity
fun divisionComplex(RealImg(a, b), RealImg(c, d)) =
RealImg ((a * c + b * d) / (c * c + d * d), ((b * c) - (a * d))/ (c* c + d * d))
However it fails with this:
Error: syntax error: inserting EQUALOP
I am very confused. Why does this happen? I know that I can't compare two reals in SML, but how am I supposed to do pattern matching with 0?
As you said SML doesn't allow to pattern match real numbers, but recommends to use Real.== instead or compare the difference between these number against some delta.
What about just using a mere if statement for this? (also some Infinity cases added just to make the match against function params exhaustive, but feel free to change it, because it doesn't pretend to be correct)
datatype complex = RealImg of real * real | Infinity;
fun divisionComplex(Infinity, _) = Infinity
| divisionComplex(_, Infinity) = Infinity
| divisionComplex(RealImg(a, b), RealImg(c, d)) =
if Real.== (c, 0.0) andalso Real.== (d, 0.0)
then Infinity
else
RealImg ((a * c + b * d) / (c * c + d * d), ((b * c) - (a * d))/ (c* c + d * d))

Maths Two Percentage Increases - Any Takers

Maths Puzzle
A = 10 (COST)
B = 20 (Sell Price)
C = 15% (Fee)
D = Tax at 20% or 1/6th if you are taking it away
E = Margin
B x C = 3.60
B / 6 in Reverse = 3.33
E = B - A - (B x C) - (B / 6) = 3.07
Ok The above works correct when i i provide B Sell Price
I want a formula that will Give me E, If i say E = 3.07 It says B = 20
How would i do that, the math
Any boffins can help
Thanks
First:
You did not use D: I suppose instead of B / 6, it should read B x D, where D can be either 20% or 16,666...%
There is a mistake: B x C is not 3.60 for the given values (B=20, C=15%), it is 3.
This is a matter of mathematical deduction:
Given the equation:
E = B - A - (B x C) - (B x D)
Add A to both sides:
E + A = B - (B x C) - (B x D)
Isolate B:
E + A = B x (1 - C - D)
Divide both sides by (1 - C - D). Condition: C + D cannot equal 100%
(E + A) / (1 - C - D) = B
So there is your formula for calculating B. Take note of the condition: this only holds true when C + D is not equal to 100%.

How to algebraically solve a system of equations?

I am not sure whether this is right place to ask. Here N, L, H, p, and d are parameters. I need to solve this system of equations. Specifically, I need to solve for b(t) and e(t).
Variables | t=1 | t>1
----------|--------|------------------------
n(t) | N |N(1-p)^(t-1)
s(t) | 1 |((1-p+dp)/(1-p))^(t-1)
b(t) | L |b(t-1)+p(H-b(t-1))
e(t) |(H-L)/2 |e(t-1)+(p(H-b(t-1)))/2
c(t) |(1-d)pN |(1-d)pN(1-p+dp)^(t-1)
Please help me how should I start this problem to solve.
Since you used a Wolfram-Mathematica tag, perhaps you intend to use Mathematica
RSolve[{b[1]==L, b[t]==b[t-1]+p(H-b[t-1]),
e[1]==(H-L)/2, e[t]==e[t-1]+p(H-b[t-1])/2}, {b[t],e[t]}, t]//FullSimplify
which returns
Solve::svars: Equations may not give solutions for all "solve" variables
{b[t]->H+(-H+L)(1-p)^(-1+t),
e[t]->((H-L)(-2+(1-p)^t+2 p))/(2(-1+p))}
It seems that these formulas give recurrent equations - you find values for t = 1 (from table), then calculate values for t = 2, then for t = 3 and so on
b(t) = b(t-1) + p * (H - b(t-1))
t = 1: L
t = 2: b(2) = b(1) + p * (H - b(1)) or
L + p * (H - L) = L + p * H - p * L
t = 3: b(3) = b(2) + p * (H - b(2))
Example: L= 2; p = 3; H = 7;
b(1) = 2
b(2) = 2 + 3 * (7 - 2) = 17
b(3) = 17 + 3 * (7 - 17) = -13

Calculating the level of insertion based on the size of the tree

If I have a graph structure that looks like the following
a level-1
b c level-2
c d e level-3
e f g h level-4
...... level-n
a points to b and c
b points to c and d
c points to d and e
and so on
how can i calculate the n from the size(number of existing nodes) of the graph/tree?
The number of nodes present if the height is h is given by
1 + 2 + 3 + ... + h = h(h + 1) / 2
This means that one simple option would be to take the total number of nodes n and do a simple binary search to find the right value of h that such that h(h + 1) / 2 = n.
Alternatively, since n = h(h + 1) / 2, you can note that
n = h(h + 1) / 2
2n = h2 + h
0 = h2 + h - 2n
Now you have a quadratic equation (in h) that you can solve to directly get back the value of h. The solution is
h = (-1 ± √(1 + 8n)) / 2
If you take the minus branch, you'll get back a negative number, so you should take the positive branch and compute
(-1 + √(1 + 8n)) / 2
to directly get back h.
Hope this helps!

No idea how to solve SICP exercise 1.11

Exercise 1.11:
A function f is defined by the rule that f(n) = n if n < 3 and f(n) = f(n - 1) + 2f(n - 2) + 3f(n - 3) if n > 3. Write a procedure that computes f by means of a recursive process. Write a procedure that computes f by means of an iterative process.
Implementing it recursively is simple enough. But I couldn't figure out how to do it iteratively. I tried comparing with the Fibonacci example given, but I didn't know how to use it as an analogy. So I gave up (shame on me) and Googled for an explanation, and I found this:
(define (f n)
(if (< n 3)
n
(f-iter 2 1 0 n)))
(define (f-iter a b c count)
(if (< count 3)
a
(f-iter (+ a (* 2 b) (* 3 c))
a
b
(- count 1))))
After reading it, I understand the code and how it works. But what I don't understand is the process needed to get from the recursive definition of the function to this. I don't get how the code could have formed in someone's head.
Could you explain the thought process needed to arrive at the solution?
You need to capture the state in some accumulators and update the state at each iteration.
If you have experience in an imperative language, imagine writing a while loop and tracking information in variables during each iteration of the loop. What variables would you need? How would you update them? That's exactly what you have to do to make an iterative (tail-recursive) set of calls in Scheme.
In other words, it might help to start thinking of this as a while loop instead of a recursive definition. Eventually you'll be fluent enough with recursive -> iterative transformations that you won't need to extra help to get started.
For this particular example, you have to look closely at the three function calls, because it's not immediately clear how to represent them. However, here's the likely thought process: (in Python pseudo-code to emphasise the imperativeness)
Each recursive step keeps track of three things:
f(n) = f(n - 1) + 2f(n - 2) + 3f(n - 3)
So I need three pieces of state to track the current, the last and the penultimate values of f. (that is, f(n-1), f(n-2) and f(n-3).) Call them a, b, c. I have to update these pieces inside each loop:
for _ in 2..n:
a = NEWVALUE
b = a
c = b
return a
So what's NEWVALUE? Well, now that we have representations of f(n-1), f(n-2) and f(n-3), it's just the recursive equation:
for _ in 2..n:
a = a + 2 * b + 3 * c
b = a
c = b
return a
Now all that's left is to figure out the initial values of a, b and c. But that's easy, since we know that f(n) = n if n < 3.
if n < 3: return n
a = 2 # f(n-1) where n = 3
b = 1 # f(n-2)
c = 0 # f(n-3)
# now start off counting at 3
for _ in 3..n:
a = a + 2 * b + 3 * c
b = a
c = b
return a
That's still a little different from the Scheme iterative version, but I hope you can see the thought process now.
I think you are asking how one might discover the algorithm naturally, outside of a 'design pattern'.
It was helpful for me to look at the expansion of the f(n) at each n value:
f(0) = 0 |
f(1) = 1 | all known values
f(2) = 2 |
f(3) = f(2) + 2f(1) + 3f(0)
f(4) = f(3) + 2f(2) + 3f(1)
f(5) = f(4) + 2f(3) + 3f(2)
f(6) = f(5) + 2f(4) + 3f(3)
Looking closer at f(3), we see that we can calculate it immediately from the known values.
What do we need to calculate f(4)?
We need to at least calculate f(3) + [the rest]. But as we calculate f(3), we calculate f(2) and f(1) as well, which we happen to need for calculating [the rest] of f(4).
f(3) = f(2) + 2f(1) + 3f(0)
↘ ↘
f(4) = f(3) + 2f(2) + 3f(1)
So, for any number n, I can start by calculating f(3), and reuse the values I use to calculate f(3) to calculate f(4)...and the pattern continues...
f(3) = f(2) + 2f(1) + 3f(0)
↘ ↘
f(4) = f(3) + 2f(2) + 3f(1)
↘ ↘
f(5) = f(4) + 2f(3) + 3f(2)
Since we will reuse them, lets give them a name a, b, c. subscripted with the step we are on, and walk through a calculation of f(5):
Step 1: f(3) = f(2) + 2f(1) + 3f(0) or f(3) = a1 + 2b1 +3c1
where
a1 = f(2) = 2,
b1 = f(1) = 1,
c1 = 0
since f(n) = n for n < 3.
Thus:
f(3) = a1 + 2b1 + 3c1 = 4
Step 2: f(4) = f(3) + 2a1 + 3b1
So:
a2 = f(3) = 4 (calculated above in step 1),
b2 = a1 = f(2) = 2,
c2 = b1 = f(1) = 1
Thus:
f(4) = 4 + 2*2 + 3*1 = 11
Step 3: f(5) = f(4) + 2a2 + 3b2
So:
a3 = f(4) = 11 (calculated above in step 2),
b3 = a2 = f(3) = 4,
c3 = b2 = f(2) = 2
Thus:
f(5) = 11 + 2*4 + 3*2 = 25
Throughout the above calculation we capture state in the previous calculation and pass it to the next step,
particularily:
astep = result of step - 1
bstep = astep - 1
cstep = bstep -1
Once I saw this, then coming up with the iterative version was straightforward.
Since the post you linked to describes a lot about the solution, I'll try to only give complementary information.
You're trying to define a tail-recursive function in Scheme here, given a (non-tail) recursive definition.
The base case of the recursion (f(n) = n if n < 3) is handled by both functions. I'm not really sure why the author does this; the first function could simply be:
(define (f n)
(f-iter 2 1 0 n))
The general form would be:
(define (f-iter ... n)
(if (base-case? n)
base-result
(f-iter ...)))
Note I didn't fill in parameters for f-iter yet, because you first need to understand what state needs to be passed from one iteration to another.
Now, let's look at the dependencies of the recursive form of f(n). It references f(n - 1), f(n - 2), and f(n - 3), so we need to keep around these values. And of course we need the value of n itself, so we can stop iterating over it.
So that's how you come up with the tail-recursive call: we compute f(n) to use as f(n - 1), rotate f(n - 1) to f(n - 2) and f(n - 2) to f(n - 3), and decrement count.
If this still doesn't help, please try to ask a more specific question — it's really hard to answer when you write "I don't understand" given a relatively thorough explanation already.
I'm going to come at this in a slightly different approach to the other answers here, focused on how coding style can make the thought process behind an algorithm like this easier to comprehend.
The trouble with Bill's approach, quoted in your question, is that it's not immediately clear what meaning is conveyed by the state variables, a, b, and c. Their names convey no information, and Bill's post does not describe any invariant or other rule that they obey. I find it easier both to formulate and to understand iterative algorithms if the state variables obey some documented rules describing their relationships to each other.
With this in mind, consider this alternative formulation of the exact same algorithm, which differs from Bill's only in having more meaningful variable names for a, b and c and an incrementing counter variable instead of a decrementing one:
(define (f n)
(if (< n 3)
n
(f-iter n 2 0 1 2)))
(define (f-iter n
i
f-of-i-minus-2
f-of-i-minus-1
f-of-i)
(if (= i n)
f-of-i
(f-iter n
(+ i 1)
f-of-i-minus-1
f-of-i
(+ f-of-i
(* 2 f-of-i-minus-1)
(* 3 f-of-i-minus-2)))))
Suddenly the correctness of the algorithm - and the thought process behind its creation - is simple to see and describe. To calculate f(n):
We have a counter variable i that starts at 2 and climbs to n, incrementing by 1 on each call to f-iter.
At each step along the way, we keep track of f(i), f(i-1) and f(i-2), which is sufficient to allow us to calculate f(i+1).
Once i=n, we are done.
What did help me was running the process manually using a pencil and using hint author gave for the fibonacci example
a <- a + b
b <- a
Translating this to new problem is how you push state forward in the process
a <- a + (b * 2) + (c * 3)
b <- a
c <- b
So you need a function with an interface to accept 3 variables: a, b, c. And it needs to call itself using process above.
(define (f-iter a b c)
(f-iter (+ a (* b 2) (* c 3)) a b))
If you run and print each variable for each iteration starting with (f-iter 1 0 0), you'll get something like this (it will run forever of course):
a b c
=========
1 0 0
1 1 0
3 1 1
8 3 1
17 8 3
42 17 8
100 42 17
235 100 42
...
Can you see the answer? You get it by summing columns b and c for each iteration. I must admit I found it by doing some trail and error. Only thing left is having a counter to know when to stop, here is the whole thing:
(define (f n)
(f-iter 1 0 0 n))
(define (f-iter a b c count)
(if (= count 0)
(+ b c)
(f-iter (+ a (* b 2) (* c 3)) a b (- count 1))))
A function f is defined by the rule that f(n) = n, if n<3 and f(n) = f(n - 1) + 2f(n - 2) + 3f(n - 3), if n > 3. Write a procedure that computes f by means of a recursive process.
It is already written:
f(n) = n, (* if *) n < 3
= f(n - 1) + 2f(n - 2) + 3f(n - 3), (* if *) n > 3
Believe it or not, there was once such a language. To write this down in another language is just a matter of syntax. And by the way, the definition as you (mis)quote it has a bug, which is now very apparent and clear.
Write a procedure that computes f by means of an iterative process.
Iteration means going forward (there's your explanation!) as opposed to the recursion's going backwards at first, to the very lowest level, and then going forward calculating the result on the way back up:
f(0) = 0
f(1) = 1
f(2) = 2
f(n) = f(n - 1) + 2f(n - 2) + 3f(n - 3)
= a + 2b + 3c
f(n+1) = f(n ) + 2f(n - 1) + 3f(n - 2)
= a' + 2b' + 3c' where
a' = f(n) = a+2b+3c,
b' = f(n-1) = a,
c' = f(n-2) = b
......
This thus describes the problem's state transitions as
(n, a, b, c) -> (n+1, a+2*b+3*c, a, b)
We could code it as
g (n, a, b, c) = g (n+1, a+2*b+3*c, a, b)
but of course it wouldn't ever stop. So we must instead have
f n = g (2, 2, 1, 0)
where
g (k, a, b, c) = g (k+1, a+2*b+3*c, a, b), (* if *) k < n
g (k, a, b, c) = a, otherwise
and this is already exactly like the code you asked about, up to syntax.
Counting up to n is more natural here, following our paradigm of "going forward", but counting down to 0 as the code you quote does is of course entirely equivalent.
The corner cases and possible off-by-one errors are left out as exercise non-interesting technicalities.

Resources